2012
DOI: 10.1111/j.1447-0756.2012.01937.x
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic adenocarcinoma of mammary‐like glands of the vulva successfully treated with surgery and hormonal therapy

Abstract: Vulvar cancer is a rare malignancy; most tumors are squamous cell type while adenocarcinomas are rare. Primary adenocarcinomas of the vulva predominantly include extramammary Paget's disease and sweat gland carcinomas. Greene first described a rare form of adenocarcinoma in 1936, which was called adenocarcinoma of mammary-like glands of the vulva because of its morphologic and immunohistochemical resemblance to breast adenocarcinomas. In the management of this entity, varying combinations of surgery, radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The main presentation was an unexplained vaginal bleeding in a previously hysterectomized elderly lady without any initially visible local lesion, while the majority of the reported cases presented with a painless vulvar mass, ranging in diameter size from 1.5 cm to 20 cm . To our knowledge, there have been 28 reported cases of primary breast carcinoma of the vulva since the first documented case by Greene in 1935 . The age of the reported cases ranged from 45 to 82 years (mean: 62 years), which is consistent with normally located breast cancer.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The main presentation was an unexplained vaginal bleeding in a previously hysterectomized elderly lady without any initially visible local lesion, while the majority of the reported cases presented with a painless vulvar mass, ranging in diameter size from 1.5 cm to 20 cm . To our knowledge, there have been 28 reported cases of primary breast carcinoma of the vulva since the first documented case by Greene in 1935 . The age of the reported cases ranged from 45 to 82 years (mean: 62 years), which is consistent with normally located breast cancer.…”
Section: Discussionmentioning
confidence: 78%
“…Given the rarity of these lesions, and the lack of standard treatment paradigm, the management of carcinoma of the ectopic breast tissue is extrapolated from the established treatment guidelines of the normally located breast cancer. Treatment modalities have ranged from wide local excision for DCIS to radical vulvectomy with bilateral inguinal nodal dissection for invasive carcinomas . Adjuvant therapies took the form of chemotherapy, radiation and hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because those lesions are rare, recommended management strategies are inconsistent. In their review, Benito et al reported approximately 25 cases overall [4]. The reported survival rates ranged between non-survivals (death from the disease) in the case reported by Fracchioli [5], to 48 months in the case reported by Diniz da Costa [6], whereas the survival rate in the Benito et al case was 24 months [4].…”
Section: Discussionmentioning
confidence: 97%
“…A recent review only identified approximately 25 cases reported in the literature (Benito et al, 2013). Management strategies have ranged from wide local excision for DCIS to radical vulvectomy with bilateral inguinofemoral nodal dissection for invasive carcinomas (Irvin et al, 1999).…”
Section: Commentmentioning
confidence: 99%